The role of macroeconomic policy in rebalancing growth - Peter J. Morgan (Asian Development Bank Institute (ADBI), 2011)
The aftermath of the global financial crisis of 2007 - 2009 has called the export-led growth model of Asian economies into question. This paper describes the contribution that macroeconomic policy can make to promote a rebalancing of growth away from dependence on exports to developed economies to a more sustainable pattern of growth centered on domestic and regional demand. This represents a significant departure from the traditional uses of macroeconomic policy to stabilize the economic cycle and achieve stable and low inflation. The evidence suggests that macroeconomic policy can successfully contribute to growth rebalancing. Policy measures not only can affect aggregate demand directly, but can also affect it indirectly via their microeconomic impacts on private sector behavior. Although in the long-term fiscal policy should be balanced to maintain government debt stability and avoid crowding out of private investment, there may be substantial scope to expand monetary and fiscal policy in the medium-term to offset the deflationary effects of an appreciating currency during periods of current account reversal. Previous experience suggests that most of the needed stimulus can be provided by monetary policy, with only a supplementary role to be played by fiscal policy. Moreover, Asian economies with large current account surpluses tend to have sufficient fiscal space. The evidence suggests that excessive savings rather than insufficient investment is the main factor behind high current account surpluses in Asian economies. This implies that measures to encourage consumption, either by raising the level of household disposable income or reducing the savings rate are likely to have the highest payoff in terms of reducing imbalances. Increased spending on social protection, including health insurance, unemployment insurance and pensions, as well as investment in education, are seen as key ways to reduce household demand for precautionary savings. Governments can raise investment spending directly through increased government investment, especially infrastructure investment. There also may be large payoffs to making investments to improve the investment climate, thereby encouraging private investment. Cuts in corporate tax rates and government support for deepening of financial markets can also encourage investment, including improving the infrastructure for corporate bond markets, developing credit databases and other infrastructure for SMEs, and developing the infrastructure for microfinance. Cuts in export subsidies and foreign exchange intervention can cut net exports directly. Improvement of frameworks for macroeconomic and financial stability can also support domestic demand by reducing uncertainty and the need for precautionary savings. This includes giving more explicit weight to financial stability as an objective of monetary policy, developing a macroprudential framework for financial surveillance and regulation, and refining policy tools for management of capital flows.
Keywords: E21; E52; E58; E62; E64; F31; F32; H50; H55; I38; 330; Exportinduziertes Wachstum; Wirtschaftskrise; Wirtschaftliche Anpassung; Wirtschaftspolitisches Ziel; Wirtschaftswachstum; Nachhaltigkeit; Asien